Pengembangan Model Hipotetik Layanan Konseling Kelompok Realitas Untuk Meningkatkan Resiliensi Diri Siswa Adem 3T di SMA Negeri 1 Sumatera Barat - Febriace Febriace; Masril Masril; Irman Irman (Jurnal Sinestesia, 2022)
The purpose of this study was to produce a hypothetical development model for reality group counseling services to increase the self-resilience of Adem 3T students at SMA Negeri 1 in West Sumatra. The research method is the development method with the R and D model by Borg and Gall, using five stages of development, namely (1) research and data collection, (2) planning, (3) product draft development, (4) expert validity test, and (5) product revision. Descriptive statistical analysis was used to analyze the research data. Based on the results of the feasibility test by experts on the hypothetical development model of reality group counseling services, the average result was 4.52, with a percentage value of 90.33% product validity, which was in the very valid eligibility criteria. Thus, it means that the product developed in the category is very feasible. It can be concluded that the development of a hypothetical model of reality group counseling services is considered very feasible in terms of content and can be used by counseling teachers to increase the self-resilience of Adem 3T students at SMAN 1 West Sumatra.